A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus - de Castro, Matheus C.; Barros, Ávyla R. A.; de Azevedo, Emiliano B.; Britto, Erika P. J.; Castilho, Raphael C.; de Moraes, Gilberto J. (Zootaxa, 2020)
Gamasellodes lavafesii Castro, Azevedo & Castilho sp. nov. is described based on the morphology of adult females collected from litter and soil in a transition region between Cerrado and Amazon Rainforest of Mato Grosso state and in the Caatinga biome of Alagoas state, respectively in midwestern and northeastern Brazil. A key for the separation of females of the 26 recognisable world species of Gamasellodes is provided.